2020
DOI: 10.1590/s0100-83582020380100019
|View full text |Cite
|
Sign up to set email alerts
|

Weed Vegetation Structure in an Area of Organic Acerola Cultivation, Parnaíba, Piauí, Brazil

Abstract: This study aimed to identify and quantify the weed species in an area of organic acerola cultivation in the Distrito de Irrigação dos Tabuleiros Litorâneos do Piauí (DITALPI) in Parnaíba, Piauí, Brazil. Phytosociological sampling was completed in the rainy season, before the farmers adopted management techniques for the plants. Thirty plots of 0.25 m2 were sampled. The plots were located between crop rows, which consisted of herbaceous-subshrub plants. The absolute and relative covers and the absolute and rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…As famílias que mais se destacaram foram Poaceae e Euphorbiaceae com 34,62% e 11,54% das espécies encontradas, respectivamente. Essas famílias são frequentemente apontadas como os principais grupos de plantas daninhas quanto ao número de espécies, tanto em cultivos de abacaxi (Sarmento et al, 2017), como em outras culturas frutíferas tais como acerola (Sousa et al, 2020), mamão (Costa et al, 2019) e banana (Ávila et al, 2020).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…As famílias que mais se destacaram foram Poaceae e Euphorbiaceae com 34,62% e 11,54% das espécies encontradas, respectivamente. Essas famílias são frequentemente apontadas como os principais grupos de plantas daninhas quanto ao número de espécies, tanto em cultivos de abacaxi (Sarmento et al, 2017), como em outras culturas frutíferas tais como acerola (Sousa et al, 2020), mamão (Costa et al, 2019) e banana (Ávila et al, 2020).…”
Section: Resultsunclassified
“…Espécies de Amaranthus sp. também foram encontradas em levantamentos realizados em frutíferas como acerola (SOUSA et al, 2020) e mamão (COSTA et al, 2019).…”
Section: Fernandes T Et Alunclassified
“…The capacity dimension (D 0 ) describes a global view of the system (Leiva et al, 2019;Siqueira et al, 2022), allowing us to verify how the scales are filled by the measurement values. Variations in D 0 values for R. raphanistrum, Commelina ssp., and OW on the sampling dates showed that the scales were filled with measurement values, indicating that the difference in D 0 values for the species under study reflects their ecology (Booth et al, 2003;Brighenti, Oliveira, 2011), mainly with regard to the aggregated distribution (Cheam, Code, 1995;Schaffrath et al, 2007;Chiba et al, 2010;Siqueira et al, 2016;Pereira et al, 2018;Izquierdo et al, 2020;Sousa et al, 2020;Jurado-Expósito et al, 2021). The D 1 dimension is related to the entropy information and quantifies the degree of disorder in the system.…”
Section: Discussionmentioning
confidence: 99%
“…As for Commelina ssp. (L.), Brighenti and Oliveira (2011) describe the species as being resistant to chemical management with glyphosate, and, according to Sousa et al (2020), its control is hindered due to the low efficiency of mechanical methods since its rapid reproduction occurs vegetatively or through seeds. Hence, during the present research period, the species with the most significant expression presented different reproductive and occupational strategies, resulting in high spatial variability and variability scale.…”
Section: Ecology and Weed Managementmentioning
confidence: 99%